The persistence of nationalism : from imagined communities to urban encounters - Stephens, Angharad Closs (London : Routledge, 2013)
'This is a book about the difficulties of thinking and acting politically in ways that refuse the politics of nationalism. It offers a detailed study of how contemporary attempts by theorists of cosmopolitanism, globalism and multiculturalism to go beyond nationalism often reproduce key aspects of a nationalist imaginary. It argues that the challenge of resisting nationalism will require more than a shift in the scale of politics--from the national up to the global, or down to the local--and more than a shift in how we count politics--to an emphasis on diversity and multiculturalism. In order to avoid the grip of'nationalist thinking', the book argues that we need to reopen the question of what it means to imagine community. It does so by way of various encounters with urban life. Set against the backdrop of the imaginative geographies of the'War on Terror', the book shows how critical interventions often work in collaboration with nationalist politics. It claims that a nationalist imaginary includes powerful understandings of freedom, subjectivity, sovereignty and political space/time which must also be placed under question if we want to avoid reproducing ideas about'us' and'them'. Drawing on insights from feminist, cultural and postcolonial studies as well as critical approaches to International Relations and Geography, this book presents a unique and refreshing approach to the politics of nationalism.'--Page 4 of cover.
Introduction: the persistence of nationalist imaginaries -- Beyond'imagined communities': nationalism and the politics of knowledge -- Weberian tales: disenchantment, mastery and meaning -- Rousseau's legacies: the politics of time, community and loss -- Urban cosmopolitanism: the return of the nation in times of terror -- Nationalism and its limits: the politics of imagination -- Sites of memory and the city as a melee -- Conclusion: the aftermath of nationalist imaginaries.
Includes bibliographical references (pages 137-153) and index.
Keywords: Nationalism; Internationalism